Isang bala ka lang part 2 ([s.l.] Viva Films, 1999)
This is the story of a dedicated, retired cop forced to join the police force anew to go after a corrupt politician.
VCD
Fernando Poe, Jr., Nanette Medved.
Keywords: Feature films; Action films